The relationship between results on the WISC-IV-HR intelligence indices and academic achievement - Matešić, Krunoslav (2012)
The adapted and standardized Wechsler Intelligence Scale for Children (WISC-IV-HR) was published in the Republic of Croatia in 2009. The norms were obtained on the basis of a stratified sample of 1200 children aged 6.0 to 16.11 years. This paper presents data on the relationship between the WISC-IV-HR intelligence indices, IQ and general half-term academic achievement in higher primary school grades (grades 5 to 8) which were included in the standardization.
Projekt MZOS
ENG